2009
DOI: 10.1007/s12160-009-9119-2
|View full text |Cite
|
Sign up to set email alerts
|

Obesity: Can Behavioral Economics Help?

Abstract: Given the limited ability of individuals to retain and use accurate health information coupled with varying levels of self control, profit motivations of marketers can become predatory--though not necessarily malicious. Alternative policy options that do not restrict choice are outlined, which enable consumers to make better decisions. These options allow for profit motivations of marketers to align with the long-term well being of the consumer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 51 publications
0
60
0
1
Order By: Relevance
“…A number of field studies reviewed by Just and Payne (2009), suggest a variety of nudge strategies that may be effective and acceptable to the consumer. These include the provision of small plates and utensils in 'all you can eat' restaurants, and positioning buffet food further away from the customers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of field studies reviewed by Just and Payne (2009), suggest a variety of nudge strategies that may be effective and acceptable to the consumer. These include the provision of small plates and utensils in 'all you can eat' restaurants, and positioning buffet food further away from the customers.…”
Section: Discussionmentioning
confidence: 99%
“…The items encountered most frequently at checkouts are magazines, chewing gum, confectionary, soft drinks and batteries (Front End Focus, 2008). These minor changes in the micro environment find reflection in the nudge theory and nudge strategies which usually consist of covert interventions that aim to change behaviour in subtle ways (Just & Payne, 2009), To date, however, there are no published studies testing the effect of nudging changes in eating behavior by locating fruit at the checkouts and removing the confectionary from the checkout area. This could be due to commercial interests that dictate maximizing profit from sales regardless of the long term consequences for the health of the population.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Cummins and his research team have shown on two occasions (2008, 2014) that even when presented with a new food source, many people do not deviate from their old habits. Assuming that storeswitching equates with dietary change ignores the imperfect choice sets enacted when in the shopping environment (Just and Payne 2009). Recognizing that people across the entire socioeconomic spectrum are subject to this imperfection, researchers and practitioners cannot fairly claim that the primary solution to food deserts should be to simply attract retail investment into underserved neighborhoods.…”
Section: Structuration Theory/habitusmentioning
confidence: 99%
“…This approach for the study of 367 delayed rewards can be extended to other domains such as reducing obesity (Just & Payne, 2009) 368 and improving cardiovascular health (Fair et al, 2008). The research in this area will probably be 369 most successful if it takes a holistic approach into account, i.e.…”
Section: Conclusion and Future Directions 366mentioning
confidence: 99%